Alien fishes in the Black Sea waters of Crimea (Ukraine) - Leonid Manilo (Geo&Bio, 2021)
The paper is devoted to alien fish species that have appeared in coastal waters of the Black Sea near Crimea for the past 50 years. The fish fauna of the Black Sea mainly comprises species that represent the Ponto-Caspian and Atlantic-Mediterranean faunal complexes. According to the generalised literature data, 158 fish species of 107 genera of 60 families have been recorded in the Black Sea since the publication of K. F. Kessler’s work (Kessler 1877), all of them representing the Atlantic-Mediterranean complex. In waters of Crimea, 116 species of 86 genera of 51 families have been recorded for the same period. A full checklist of fishes of this complex is presented indicating 31 alien species that have appeared since the 1970s and which belong to 27 genera and 16 families. In waters of Crimea, alien fishes make up 26.5 % of all species, 31.0 % of all genera, and 31.4 % of all families of the Atlantic-Medirranean complex. According to the level of their occurrence in marine waters of Crimea, all recently introduced species are grouped into three categories: regular, sporadic, and casual. Their brief characterisics are given, including synonymy, representation in the fish collection of the NMNH NASU, brief description, distribution, and vector of introduction. It was found that benthic species predominate among introduced fishes that occur regularly in waters of Crimea (12 species, or 80.0 %), while bentho-pelagic and pelagic species are less represented (6.7 % and 13.3 %, respectively). Pelagic and bentho-pelagic species prevail (50.0 % and 37.5 %, respectively) among fishes that occur sporadically. Bentho-pelagic species predominate (57.1 %) among fishes that occur casually. It was discovered that among the 31 alien fishes recorded in the Black Sea waters of Crimea for the past 50 years predominate those that have appeared here due to the natural process of mediterranisation (22 species, 71.0 %). It was imposibble to determine the vector of introduction of 4 species (12.9 %). The appearance of 5 species, which represent 16.1 % of all alien species, is related to anthropogenic factors. It can be also concluded that benthic species predominate among the alien fishes (14 species, or 45.2 %), while bentho-pelagic (9 species) and pelagic (8 species) fishes make up 29.0 % and 25.8 %, respectively. Of the 31 introduced fishes, 10 (32.2 %) have naturalised and acclimatised in marine waters of Crimea and have founded independent breeding populations. Among them, representatives of the family Gobiidae notably prevail, followed by the taxonomically close family Oxudercidae, whereas one species belongs to the family Blenniidae. The so-iuy mullet, which is the only representative of the pelagic ecological group, was introduced intentionally.